Investigation of poultry slaughterhouse waste stream to produce bio-fuel for internal utilization. (May 2022) - Ozdemir, Saim; Şimşek, Aslı; Ozdemir, Serkan; Dede, Cemile
Abstract: Poultry slaughterhouses generate an abattoir sludge (PAS) that needs proper management in the principles of circular economy and green deal goals that imply a net-zero emissions, more resource efficient and sustainable economy. This study proposes a waste-to-energy approach as a sustainable strategy for water heating by utilizing waste stream and internal usage in poultry slaughterhouse sector. In the study, energy crop Arundo donax (AD) biomass produced by irrigating treated abattoir waste water and solar dried PAS were used to produce bio pellet for the boiler heater. The solar dried PAS and grinded AD straw were extruded into pellets using a real industrial press at biomass combustion plants using i) 100% PAS:0% AD, ii) 50% PAS:50% AD, iii) 0% PAS:100% AD. The calorific value, bulk density, and energy density of the PAS, AD and PAS + AD pellets were in the range of 16.81–28.78 MJ kg −1, 646–779 kg m −3, and 10.86–22.71 GJ m −3, respectively. Combustion image analysis results indicated the better flame richness and red color intensity of PAS + AD pellets than the both PAS and AD. Based on the results, almost 58% of the daily used fossil fuel coal for hot water production can be replaced by renewable PAS + AD pellets.